Deployment of Automation Software in Professional Institutions-A Case Study - Murthy, A. V. S. (Journal of Engineering Education Transformations, 2006)
College students are required to carry a variety of cards such as college i-card, library. card, bus pass, etc. This paper describes the development of a 'smart card' which replaces all cards described above and also acts as a debit card in college stationary stores and college canteen. Scope for further Improvement includes using it to mark attendance, internet access, etc.